Adverse pulmonary effects after oral exposure to copper, manganese and mercury, alone and in mixtures, in a Spraque-Dawley rat model. (4th May 2023) - Draper, M; Bester, Mj; Van Rooy, M; Oberholzer, Hm
ABSTRACT: The rise in respiratory disease has been attributed to an increase in environmental pollution. Heavy metals contribute to environmental contamination via air, water, soil and food. The effects of atmospheric exposure to heavy metals on pulmonary structure and function have been researched, but the effects through drinking water have been neglected. The aim of this study was to investigate the potential in vivo alterations in the pulmonary tissue of male Sprague-Dawley rats after a 28-day oral exposure to copper (Cu), manganese (Mn) and mercury (Hg), alone and in mixtures, at 100 times the World Health Organization's (WHO) safety limit for each heavy metal in drinking water. Forty-eight male Sprague-Dawley rats were randomly divided into eight groups (n = 6): control, Cu, Mn, Hg, Cu + Mn, Cu + Hg, Mn + Hg and Cu, Mn + Hg. The morphology of lung tissue and the bronchioles were evaluated using light- and transmission electron microscopy. For all exposed groups, morphological changes included thickened inter- and intra-alveolar spaces, stratified epithelium, disrupted smooth muscle and early fibrosis and desquamation of the epithelia of the bronchioles to varying degrees. In all exposed groups, ultrastructurally, an increase in disarranged collagen and elastin fibers, nuclear membrane detachment, chromatin condensation, indistinct nucleoli and an increase in collagen fiber disarrangement was observed. This study has identified that oral exposure to Cu, Mn and Hg and as part of mixtures caused pathogenesis due to inflammation, cellular damage and fibrosis with Mn + Hg being the most potent heavy metal group.